Glucocorticoids attenuate acute graft‐versus‐host disease by suppressing the cytotoxic capacity of CD8+ T cells. Issue 4 (7th January 2015) - Theiss‐Suennemann, Jennifer; Jörß, Katharina; Messmann, Joanna J; Reichardt, Sybille D; Montes‐Cobos, Elena; Lühder, Fred; Tuckermann, Jan P; AWolff, Hendrik; Dressel, Ralf; Gröne, Hermann‐Josef; Strauß, Gudrun; Reichardt, Holger M
Abstract Glucocorticoids (GCs) are released from the adrenal gland during inflammation and help to keep immune responses at bay. Owing to their potent anti‐inflammatory activity, GCs also play a key role in controlling acute graft‐versus‐host disease (aGvHD). Here we demonstrate that mice lacking the glucocorticoid receptor (GR) in T cells develop fulminant disease after allogeneic bone marrow transplantation. In a fully MHC‐mismatched model, transfer of GR‐deficient T cells resulted in severe aGvHD symptoms and strongly decreased survival times. Histopathological features were aggravated and infiltration of CD8+ T cells into the jejunum was increased when the GR was not expressed. Furthermore, serum levels of IL‐2, IFNγ, and IL‐17 were elevated and the cytotoxicity of CD8+ T cells was enhanced after transfer of GR‐deficient T cells. Short‐term treatment with dexamethasone reduced cytokine secretion but neither impacted disease severity nor the CTLs' cytolytic capacity. Importantly, in an aGvHD model in which disease development exclusively depends on the presence of CD8+ T cells in the transplant, transfer of GR‐deficient T cells aggravated clinical symptoms and reduced survival times as well. Taken together, our findings highlight that suppression of CD8+ T‐cell function is a crucial mechanism in the control of aGvHD by endogenous GCs. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.